Smart street light / Mohamad Hazim Johari & Muhammad Hazwan Mohd Zulkifly - Johari, Mohamad Hazim; Mohd Zulkifly, Muhammad Hazwan (2015)
This system is designed for outdoor application in un-electrified remote rural areas. This system is an ideal application for campus and village street lighting. The system is provided with battery storage backup sufficient to operate the light for 10-11 hours daily. The project is about to develop and fabricate the circuit that can charge the lead acid battery during day time by using solar as the source. When the lead acid batteries reach the limit voltage, we use diode to prevent excess voltage from charging the solar panel. For the switching, we used PIC 16F877 A to switch on the lamp, by using the photocell sensor. The PIC16F877A will determine whether it is daytime or night time. The light will automatically on when the photocell sensor give the input to the PIC and PIC will give the output to the Liquid Crystal Display (LCD) to show the Analogue to- Digital (AID) value. At the same time the PIC will give the AID value to the LED and this value will be send to Pulse Width Modulation (PWM) to control the intensity of LED. PWM control the intensity by controlling the voltage of LDR. When night change to the day, photocell sensor detect the ray from the sun; PIC will give the output to off the lamp and the charging circuit will continue charge the battery for the day. Lastly, the LCD will produce an output to the road user.